RESEARCH INNOVATION FOR SUSTAINABLE EDUCATION CULTURE (RISE2045) DI STAIN MADINA: KOLABORASI RISET DAN TEKNOLOGI MENUJU PENDIDIKAN BERKELANJUTAN - Fahmi, Zul; Husaini, Aisyah (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to describe the initial state of the research ecosystem at STAIN Mandailing Natal, to assess student participation in scholarly activities, and to identify the primary obstacles encountered. Employing a qualitative methodology with case‑study and literature‑review approaches, primary data were gathered through direct observation, in‑depth interviews, and questionnaires administered to 360 students, while secondary data were derived from peer‑reviewed journal articles, books, and other relevant documents. The findings reveal that only approximately 10 % of the institution’s 3,800 students, across 20 degree programmes, actively engage in scholarly writing. In response, the RISE2045 initiative established “RISE Clubs” to foster a student‑centred research ecosystem, comprising brief methodological workshops, regular peer‑review circles, and an internal e‑repository. During the three‑month pilot in the History and Islamic Philosophy programme, 60 participants were recruited; 30 manuscripts underwent peer review, 17 were selected as “best drafts,” and subsequently uploaded to the platform. Post‑pilot surveys indicate that 85 % of participants reported improved writing skills and 70 % expressed greater confidence in submitting their work to academic journals. The RISE Club model is both adaptable and scalable to other programmes with local customization, and its sustainability depends on multi‑stakeholder collaboration, including funding support, adequate IT infrastructure, and engagement from the broader research community. These results underscore the effectiveness of RISE Clubs in cultivating an inclusive and enduring research culture. It is recommended that local governments strengthen support through mini‑grants, universities secure subscriptions to international journals, and other institutions adopt this model to stimulate student research activity in advance of Indonesia’s Golden Generation in 2045.